Do Individual Differences in Physical Therapists' Skills Affect Postoperative Results of Total Knee Arthroplasty? - Fujii, Tadashi; Nishio, Naoyuki; Bandou, Minenari; Kitano, Shuji; Noboru, Marehoshi; Seko, Munehito; Inagaki, Yusuke; Tanaka, Yasuhito (The Journal of Knee Surgery, 2020)
We investigated variations in postoperative outcomes of total knee arthroplasty which were dependent on the physical therapist (PT) who performed rehabilitation while keeping other parameters as uniform as possible. Seventy-nine among 690 knees were selected based on strict inclusion and exclusion criteria. Patients were randomly assigned to five PTs, who had from 2 to 21 years of experience. Range of motion (ROM) on postoperative days (PODs) 1, 3, 7, and 14 and at postoperative months 3, 6, and 12, results of timed up and go (TUG) test on POD 14, time to walking with a single cane, and time to climbing stairs, were evaluated. There were significant differences until POD 3, and no significant differences afterward in flexion. There was a significant difference on POD 1 only in extension. The TUG test showed no significant difference, but there were significant differences at the time of walking with a single cane and climbing stairs. The time taken to achieve rehabilitation, which was determined subjectively by each PT, differed among therapists, but differences in ROM were present in early period. Therefore, ROM after surgery is not affected by differences between PTs.
Keywords: total knee arthroplasty; rehabilitation; range of motion; physical therapist